The Effect of Audit Quality, Liquidity, Solvability, and Profitability on Audit Going Concern Opinion - Muhammad Faisol Himam; Endang Masitoh (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
Bankruptcy entities in Indonesia one reason is the weakness of the auditor in detecting problems that exist in the company, the auditor should be able to reveal the truth to clients about the problems that occur in the company because it has the responsibility to evaluate whether a company has the ability to survive for a certain period of time , This study aimed to analyze the effect of audit quality, liquidity, solvency, and profitability on a going concern audit opinion. In this study, the type of data is quantitative data with a population of companies manufacturing base and chemical industry sectors listed on the Indonesia Stock Exchange in 2013-2017. The samples were conducted with a purposive sampling method to obtain 18 companies for 5 years. Data analysis methods used were descriptive statistics, hypothesis testing by logistic regression. Based on the analysis it is concluded that the quality of audit does not affect the going concern audit opinion, the liquidity negatively affect the going concern audit opinion, while the solvency and profitability does not affect the going concern audit opinion.